Association between periodontal disease and systemic inflammation in patients on chronic hemodialysis // Asociación entre enfermedad periodontal e inflamación sistémica en pacientes en hemodiálisis crónica - Viana-Rojas, Jesús Antonio; Gordillo-Moscoso, Antonio; López-Quijano, Juan Manuel; Portillo-Martínez, Zulia; Pozos-Guillén, Amaury; Cepeda-Bravo, Juan Antonio; Carrillo-Calvillo, Jorge; Chevaile-Ramos, Alejandro (Investigación Clínica, 2020)
Abstract. Previous studies have demonstrated that severe chronic periodontitis is associated with an increased risk of cardiovascular mortality in the hemodialysis population. However, the association between periodontal disease and systemic inflammation in these patients is not yet fully understood. C - reactive protein (CRP) is one of the plasma proteins that appear in the acute phase of inflammation. Periodontitis is associated with elevated levels of CRP in adults and with its decrease after treatment. The aim of this study was to evaluate the association between periodontal disease and systemic inflammation in patients on chronic hemodialysis (HD). An analytical cross-sectional study was carried out on 111 outpatients with end-stage renal disease (ESRD) on chronic HD. Periodontal disease was measured by periodontal pocket depth (PPD), loss of clinical attachment level (CAL), gingival index, and plaque index. Systemic inflammation was measured by high-sensitivity C-reactive protein (hs-CRP) levels. A multivariable linear regression model was created using hs-CRP as the dependent variable. Eighty-four patients with low hs-CRP levels (≤1 mg/dL) and 27 patients with high hs-CRP levels (>1 mg/dL) were included. Patients with high hs-CRP were older, with diabetes, and with higher scores in oral health indexes. hs- CRP levels had a significant positive correlation with age, gingival index, PPD, and loss of clinical-attachment level. Finally, regression identified PPD and diabetes as independent hs-CRP contributors. In patients on chronic HD, PPD is an independent contributor of systemic inflammation. Resumen. Estudios anteriores han demostrado que la periodontitis crónica grave se asocia con un mayor riesgo de mortalidad cardiovascular en la población en hemodiálisis. Sin embargo, la asociación entre la enfermedad periodontal y la inflamación sistémica en estos pacientes aún no se conoce completamente. La proteína C-reactiva (PCR) es una de las proteínas plasmáticas que aparecen en la fase aguda de la inflamación. La periodontitis se asocia con niveles elevados de PCR en adultos y con su disminución después del tratamiento. El objetivo del estudio fue evaluar la asociación entre la enfermedad periodontal y la inflamación sistémica en pacientes con hemodiálisis crónica. Se realizó un estudio analítico de corte transversal en 111 pacientes ambulatorios con enfermedad renal en etapa terminal en hemodiálisis crónica. La enfermedad periodontal se midió por profundidad de bolsa periodontal (PBP), pérdida del nivel de inserción (PNI), índice gingival e índice de placa. La inflamación sistémica se midió por niveles de proteína C-reactiva de alta sensibilidad (PCRas). Se creó un modelo de regresión lineal multivariado utilizando PCR-as como variable dependiente. Se incluyeron 84 pacientes con bajos niveles de PCR-as (≤1 mg/dL) y 27 pacientes con niveles altos de PCR-as (>1 mg/dL). Los pacientes con PCR alta fueron mayores, con diabetes y con mayores puntajes en los índices de salud oral. Los niveles de PCR-as tuvieron una correlación positiva significativa con la edad, el índice gingival, la PBP y la PNI. Finalmente, la regresión identificó PBP y diabetes como colaboradores independientes de PCR-as. En pacientes con hemodiálisis crónica, la PBP contribuye de manera independiente a la inflamación sistémica.